PENGARUH PENGGUNAAN KNEE DECKER TERHADAP NYERI LUTUT SAAT MENDAKI GUNUNG MAHASISWA PENCINTA ALAM - Prasetyo Catur Utomo; Muhibbah Fatati; An-nisa Octaviani Putri (Medical Journal of Nusantara, 2025)
Background: One of the student activities related to physical activity and sports is mountain climbing. Mountain climbing is a sport related to physical activity and nature. Physical activity carried out in the open air has more benefits for physical and psychological health because mountain climbing is a medium to find a calm and quiet atmosphere because the mountain is far from the hustle and bustle of the city. However, mountain climbing can cause various health problems if done without good preparation. One of the physical problems that arises is knee pain. Efforts to reduce the level of pain can be done by using an assistive device (orthosis), namely knee support or elastic knee decker. Elastic knee decker is an orthosis that covers the knee area where the function of the elastic knee decker itself is to provide compression, knee stability, minimize muscle work and can reduce the degree of pain. The purpose of this study was to determine the effect of knee decker on knee pain that occurs when climbing mountains. Methods and subjects: This study is a quasi-experimental study with a two-group pre-test post-test design. Sampling using purposive sampling of 16 people. Results: The Mann-Whitney test results showed a sig. value of 0.001, meaning p<0.05, which indicates the effect of using elastic knee decker on knee pain in mountain climbers.